2010
DOI: 10.1177/1743872109349104
|View full text |Cite
|
Sign up to set email alerts
|

Degrees of Emotion: Judicial Responses to Victim Impact Statements

Abstract: Emotional standards and hierarchies in the courtroom may affect judicial reactions to victim impact statements. Based on judicial conversations and courtroom observations in two judicial districts in Minnesota, we suggest that judges contrast emotion with reason in order to maintain control of their courtrooms; when faced with emotional expressions in victim impact statements, judges appreciate expressions of compassion and tolerate expressions of grief but are uncomfortable with expressions of anger. These ju… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 2 publications
0
31
0
Order By: Relevance
“…Support from real-life settings for the idea that victims are generally expected (and hence 'prescribed') to express the first class of emotions rather than the second can be found in a series of interviews with US district court judges, conducted by Schuster and Propen (2010). These authors found that judges believe that expressions of grief (especially when related to loss of life but not expressed in an excessive manner) are more appropriate in the setting of the courtroom than expressions of anger.…”
Section: The (Ideal) Emotional Victimmentioning
confidence: 99%
“…Support from real-life settings for the idea that victims are generally expected (and hence 'prescribed') to express the first class of emotions rather than the second can be found in a series of interviews with US district court judges, conducted by Schuster and Propen (2010). These authors found that judges believe that expressions of grief (especially when related to loss of life but not expressed in an excessive manner) are more appropriate in the setting of the courtroom than expressions of anger.…”
Section: The (Ideal) Emotional Victimmentioning
confidence: 99%
“…An "emotional regime," defined in the introduction, is comparable to "emotionology" (Fineman, 2010;Schuster & Propen, 2010), but the term regime underscores that discursive knowledge informs the sociocultural construction of these rules (cf. Foucault, 1976).…”
Section: Sociology Of Emotionmentioning
confidence: 99%
“…The emotion needs to be managed in line with the emotional regime governing the situated interaction (here, the performance of judicial reason) but, as shown by Schuster and Propen (2010), the overall emotional regime of the society in which the court is embedded also matters. One example is the judge being overwhelmed by anger at a lawyer, as related before (Maroney, 2012), signifying an emotion that is external and disruptive of the action focus.…”
Section: Sociology Of Emotionmentioning
confidence: 99%
“…He describes how the narrative storytelling of lay people conflicts with legal case making. Schuster and Propen (2010) combined judicial conversations with courtroom observations to examine the emotions that victim impact statements bring into the courtrooms and their impact on judicial decision making.…”
Section: Observational Research In Courtsmentioning
confidence: 99%